Integrating Arabic Cultural Heritage Into Civic Education Curricula: Implications For Identity And Social Cohesion In Nigeria - Sule Muhammad; Ahmad Kainuwa Ph.D (Penerbit Hellow Pustaka, 2025)
This study explores the integration of Arabic cultural heritage into civic education curricula in Nigeria and its implications for identity formation and social cohesion. In a country marked by ethno-religious diversity and socio-political fragmentation, civic education is a crucial tool for promoting national unity, democratic participation, and inclusive citizenship. Northern Nigeria, with its deep-rooted Arabic-Islamic traditions, presents an opportunity for aligning civic education with learners’ cultural contexts. Drawing on socio-cultural and constructivist learning theories, the study argues that embedding Arabic values such as ‘adl (justice), shura (consultation), and mas’uliyyah (responsibility) can make civic education more relevant, relatable, and transformative. These values, historically embedded in Quranic and Tsangaya school systems, offer a culturally resonant foundation for teaching civic virtues. The integration fosters a sense of belonging and cultural affirmation among Arabic-speaking and Muslim learners, thereby enhancing their civic engagement and identification with national ideals. However, the study also identifies critical challenges, including resistance due to Nigeria’s secular educational policy, lack of teacher capacity, curriculum imbalance, and sociopolitical sensitivities. To address these issues, the study recommends inclusive curriculum frameworks, teacher training in culturally responsive pedagogy, development of localized learning materials, and stakeholder engagement. Ultimately, the paper posits that incorporating Arabic cultural heritage into civic education is not a religious imposition but a culturally grounded strategy to bridge educational gaps and promote unity in Nigeria’s pluralistic society.